EVALUASI PELAKSANAAN SISTEM RUJUKAN PESERTA BPJS KESEHATAN TERHADAP RASIO RUJUKAN NON SPESIALISTIK (RRNS) DI PUSKESMAS X TAHUN 2023 - Salma Rachim Habibah (2023)
Non-specialist referral ratio is one of capitation payment indicators that Puskesmas must achieve. Puskesmas achievements for the non-specialist referral ratio in 2022 is still in 2-2.5% and has not shown significant changes on it, so Puskesmas has not optimizing gatekeeper function on primary level. This research aimed to review the suitability of BPJS referrals implementation at Puskesmas in 2023. This study is qualitative research with a descriptive study design. Research data assembled through interviews and observation methods. Eight informants on study selected using a purposive sampling. The results given are for input variables (health workers, medicines, medical devices, standard operating procedures) that have adjusted the BPJS and national standards. The process variable shows implementation process has referred to the national reference implementation standards and BPJS Health provisions. For output variable, currently it has achieve the BPJS target of below the 2% rate. The conclusions obtained are that the input and process variables have comfor the national referral provisions and BPJS standards, and the output achievements of the Puskesmas have met BPJS regularity. Therefore, Puskesmas must improve the resource provision by adjusting the competencies and needs at the primary level.